2020
DOI: 10.1063/1.5138696
|View full text |Cite
|
Sign up to set email alerts
|

“Ester”—A new ring-shear-apparatus for hydrate-bearing sediments

Abstract: Movable holder for a quartz crystal microbalance for exact growth rates in pulsed laser deposition Review of Scientific Instruments 91, 065003 (2020);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In addition, Stern et al [55] suggested a special CH 4 hydrate formation technique called the "ice-seeding" method, which was originally designed to generate core-scale CH 4 hydrate samples from ice seed (pure H 2 O), for further mechanical testing and the investigation of hydrate dissociation patterns. Although this method is rarely used to form CH 4 hydrates, Spangenberg et al [56] employed the "ice-seeding" method in combination with partial freezing to form CH 4 hydrates in sand samples.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Stern et al [55] suggested a special CH 4 hydrate formation technique called the "ice-seeding" method, which was originally designed to generate core-scale CH 4 hydrate samples from ice seed (pure H 2 O), for further mechanical testing and the investigation of hydrate dissociation patterns. Although this method is rarely used to form CH 4 hydrates, Spangenberg et al [56] employed the "ice-seeding" method in combination with partial freezing to form CH 4 hydrates in sand samples.…”
Section: Introductionmentioning
confidence: 99%
“…Submarine landslide is a potential risk to commercial production of hydrate. To test the residual strength of HBS under larger deformations, such as submarine landslides, some scholars [31,115] have performed some basic work on the development of ring-shear devices and mechanical research (Table 4). Spangenberg et al (2020) developed a constant-temperature ring-shear instrument to determine the residual strength of hydrate or ice-containing sediments (Figure 12) [31].…”
Section: Development Of Ring Shear Test Methodsmentioning
confidence: 99%
“…In addition, the triaxial and direct shear test techniques are mainly used in measuring the elastic-plastic deformation behavior of HBS [29,30]. For analyzing the mechanical parameters of HBS in a large deformation, ring shear has been widely used to test residual deformation [31].…”
Section: Introductionmentioning
confidence: 99%
“…While, the weak cementation, low permeability, and high fine content behaviour of HBS may lead to sand production (Lu et al, 2019), wellbore collapse and formation instability (Wu et al, 2019;Li et al, 2016;Wu et al, 2023b) during the fracturing stimulation operation. Although the innovative experimental apparatus for sand production (Lu et al, 2021a(Lu et al, , 2018, cavitating jet (Zhang et al, 2020), mechanical behaviour (Seol et al, 2019;Spangenberg et al, 2020;Li et al, 2019) and kinetics behaviour (Masoudi et al, 2019) of HBS were developed, it is still hard to evaluate the fracturing performance (like fracture generation, growth and determination) in HBS. Meanwhile, proppants are widely applied in hydraulic facture fluids to increase the permeability of unconventional reservoirs (Ahmed Hafez Abdelaziz, 2020;Wang et al, 2023a, b).…”
mentioning
confidence: 99%